A précis of Gill-Oxygen Limitation Theory (GOLT), with some Emphasis on the Eastern Mediterranean - PAULY, DANIEL (Mediterranean Marine Science, 2019)
A summary of the Gill-Oxygen Limitation Theory (GOLT) is presented, i.e., of a theory seeking to explain a variety of life processes in fish and aquatic invertebrate by the fact that that the surface of their gills (and hence their oxygen supply) cannot, as 2-dimensional objects, keep up with the growth of their 3-dimensional bodies, and thus with their oxygen requirements. Various processes and attributes of fish and aquatic invertebrates are presented which had to date no mechanistic explanation, but which fit within the GOLT, offered here as a tool to interpret phenomena that until now were perceived as unrelated. However, the GOLT should also help to address practical problems, such as arise for fish farming when water temperature increases because of global warming.